Aplikasi Qiyas dalam Ekonomi Islam - Zainil Ghulam (IQTISHODUNA: Jurnal Ekonomi Islam, 2018)
Islam is the most perfect religion. It can be seen from how Islamic law was born and applied. Accordingly it support syar’i legitimacy, above of all, Islamic law protects the sake of human being indeed. Methodologically and operationally, Qiyas is an effort to connect one event with another event that has legal justification by seeing the existence of the legal causation ('illat). With the existence of this case equation, then the first case was established and given its legal provisions. Imam Shafi'i as the first pioneer of this method (Qiyas) makes a strict qualification of the elements that exist in Qiyas. In the opinion of him, Qiyas is applicable and therefore has valid legal force if the four terms and conditions are met. Including, ashl, hukm furu’ and 'illat. The dynamics of the contracts in Islamic economics, especially in contemporary finance, have developed and innovated. Therefore, it takes carefulness in searching and formulating epistemology of them. In this context, Shariah bankers creatively offering Shariah product’s contracts legally based on Qiyas method.